Mathematical Literacy in Solving PISA Space and Shape Problems : A Self-Regulation Perspective - Zainuddin Untu; Tri Widyasari; Intan Dwi Hastuti; Sutarto Sutarto; Percy Sepeng; Dian Kurniati; Sharifah Osman (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to explore the role of self-regulation in enhancing mathematical literacy among high school students solving PISA Space and Shape problems. Employing a qualitative descriptive approach, data were collected through self-regulation questionnaires, PISA-based tasks, and semi-structured interviews from high school students categorized into high, moderate, and low self-regulation groups. The data analysis technique in this study consisting of three stages: data condensation, data display, and conclusion. Results reveal a strong correlation between self-regulation and mathematical literacy, with high self-regulation students excelling in formulating, employing, and interpreting mathematical problems. Moderate self-regulation students displayed partial success, while low self-regulation students struggled significantly, particularly in interpreting and validating solutions. The study underscores the importance of self-regulation strategies such as goal-setting, monitoring, and reflection in improving mathematical literacy. Instructional recommendations include structured goal-setting frameworks, reflective practices, and scaffolded tasks to support learners with varying self-regulation levels. These findings contribute to mathematics education by addressing the interplay between self-regulation and problem-solving in the underexplored Space and Shape domain. Future research should expand on these insights through larger, longitudinal studies to further validate the implications of self-regulation in educational contexts.